5 - Cost-Sharing in Higher Education in Tanzania: Fact or Fiction? Johnson Ishengoma - M. Johnson Ishengoma, (Journal of Higher Education in Africa, 2004)
In the early 1990s, Tanzania reintroduced a policy of higher educational cost-shar- ing, designed to slowly move some of the costs of higher education, which in recent years had been borne almost exclusively by the government, toward parents and students as well as toward other nongovernmental parties. This article reports research into the difference this policy seems to have made at Tanzania’s major public university, the University of Dar es Salaam (UDSM), with particular atten- tion to the enrollment of privately sponsored (i.e., fee-paying) students and other changes discernable in university finances during the early years of this policy implementation. The report concludes that cost sharing in higher education in Tan- zania is justified on the grounds of the sheer need for nongovernmental revenue for public higher education institutions because of the declining government ap- propriations to these institutions, along with the dire need to expand access to higher education; however, its implementation has been lackadaisical.